The Society of Jesus In India And the College of São Paulo In Goa: Experiences From 1552 To 1558: A Companhia de Jesus na Índia e o Colégio de São Paulo em Goa: vicissitudes de 1552 a 1558 (Revista de História da UEG (REVHIST), 2022)
The Jesuit presence in the State of India dates back to 1542, when Francisco Xavier arrived in Goa. In 1548, the Jesuits founded the College of São Paulo, which became the reference center for the activities of the Society of Jesus in the East. The objective of this work is to discuss the College of São Paulo and the activities undertaken through it in the period between 1552 and 1558. In 1552 Francisco Xavier sets out on his mission to China, leaving Father Gaspar Barzeo in his place. Xavier's death still occurs in 1552 and that of Barzeo in 1553. After that, there is a period that we call in the work as a “command vacuum” in the Jesuit hierarchy in India, only remedied with the arrival of the new provincial and rector, in 1558. The sources used are contained in volumes II, III and IV of the Documenta Indica and in volume V of the Documentation for the history of the missions of the Portuguese Patronage of the East. It is concluded that the activities undertaken by these priests are, above all, cultural, religious and educational activities. Looking at these activities and their impacts on the local society at the time helps us to understand the dynamics of social and cultural interactions and power relations existing in the period studied.Key words: College of São Paulo. Company of Jesus. Goa. State of India.